Study of the properties of anp fertilizer encapsulated with the use of modified waste of pet - Nahurskyy, Oleh; Malovanyy, Myroslav; Synelnikov, Serhiy; Tymchuk, Ivan; Krylova, Galyna (Видавництво Львівської політехніки, 2020)
The experimental investigation of the solubility of the prolonged-action nitroamophos obtained with the use of modified polyethylene terephthalate (PET) waste is presented. The kinetic coefficients of the diffusion process of the substances inside the shell are determined. The possibility of applying a theoretical model to predict the agro-ecological properties of encapsulated ammonium nitrate phosphate is demonstrated.
Keywords: encapsulated ANP fertilizer; dissolution; kinetics; PET waste